2014
DOI: 10.3389/fendo.2014.00119
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Autonomic Neuropathy Contributes to Sleep Apnea in Young and Lean Type 1 Diabetes Mellitus Patients

Abstract: Knowledge about association between sleep apnea and cardiovascular autonomic neuropathy (CAN) in type 1 diabetes mellitus (T1DM) might give some insight into the pathogenesis of this condition in these patients. In obese patients, excessive central adiposity, including a large neck circumference, can contribute to obstructive sleep apnea (OSA). Its presence in non-obese patients, however, indicates that it could be correlated with autonomic neuropathy. The aim of this study was to compare the prevalence of OSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 22 publications
0
42
1
Order By: Relevance
“…While obesity is a major risk factor for OSA, Janovsky et al showed that OSA was common in lean patients with T1DM and that OSA can be associated with CAN 65. Unpublished data from our group showed that OSA was associated with weaker sympathetic and parasympathetic tone in patients with T2DM and that patients who were compliant with OSA treatment (continuous positive airway pressure) had improvements in several autonomic parameters over the follow-up period 66,67…”
Section: Pathogenesis Of Canmentioning
confidence: 67%
“…While obesity is a major risk factor for OSA, Janovsky et al showed that OSA was common in lean patients with T1DM and that OSA can be associated with CAN 65. Unpublished data from our group showed that OSA was associated with weaker sympathetic and parasympathetic tone in patients with T2DM and that patients who were compliant with OSA treatment (continuous positive airway pressure) had improvements in several autonomic parameters over the follow-up period 66,67…”
Section: Pathogenesis Of Canmentioning
confidence: 67%
“…The precise basis of the association between diabetes and OSA is unknown and could be driven by mechanical (secondary to obesity), metabolic (hyperglycaemia‐induced neuropathy) and/or inflammatory processes . OSA, obesity and Type 2 diabetes are probably linked by increased systemic inflammation , while Type 1 diabetes is linked to OSA through autonomic neuropathy . Aurora and Punjabi suggested the inflammatory effects of OSA may result in glucose metabolism dysfunction and eventually lead to Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…These relatively straightforward methods should be simple to use within the primary care setting, as a first step to diagnosing OSA. Given the high prevalence of OSA reported in some studies of people with Type 1 diabetes and its relative under‐detection in routine clinical practice, a case could also be made for application of such questionnaires in the care of those with Type 1 diabetes, irrespective of their BMI .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…van Dijk et al 44 did not find significant differences in scores on a measure of sleep disturbance, but they found that more adults with T1DM met the clinical cutoff for impairment relative to those without diabetes. Janovsky et al 48 reported that a greater number of adult patients with T1DM met the cutoff on a measure of sleepiness than those without T1DM. In the aforementioned study that compared individuals with T1DM to a convenience sample from different age spans, adults who had T1DM evidenced more sleep-related complaints.…”
Section: Sleep Disturbancesmentioning
confidence: 99%